Parental mental disorders and suicidal behavior in the Nigerian survey of Mental health and well-being (2011)
The objective of this study was to determine which parental mental disorders predict offspring suicidal behavior in a general adult population sample of a sub-Saharan African country. The World Health Organization Composite International Diagnostic Interview, version 3 was used to assess respondents’ suicidal behaviors as well as psychopathology in their parents. The effects of parental disorders in predicting offspring suicide ideation and attempts were examined in a series of bivariate and multivariate models. Sections on suicidality were dministered to the entire sample (n=6752), but associations with parental psychopathology were examined in a subsample of respondents (n=2143). Lifetime prevalence (95% confidence interval) of suicide ideation, plans, and attempts was 3.2% (1.4–6.5), 1.0% (0.4–7.5), and 0.7% (0.5–1.0) respectively. Parental panic disorder and substance abuse were associated with suicide ideation in offspring, but only parental panic disorder was linked to suicide attempts. Parental panic disorder predicted the onset and persistence of suicide ideation and attempts and also which persons with suicide ideation go on to make a suicide attempt. This study further affirms findings from previous studies of the role of disorders characterized by anxiety and impulse control in suicide attempts and as being a probable link in the transmission of suicidal behavior to offspring.